Experimentally Derived Intermediate to Silica-rich Arc Magmas by Fractional and Equilibrium Crystallization at 1·0 GPa: an Evaluation of Phase Relationships, Compositions, Liquid Lines of Descent and Oxygen Fugacity. (16th February 2018) - Ulmer, Peter; Kaegi, Ralf; Müntener, Othmar
Abstract: Differentiation of hydrous primary, mantle-derived magmas is a fundamental process to generate evolved intermediate to SiO2 -rich compositions forming the bulk of the continental and island arc crust. This study focuses on the results of equilibrium and fractional crystallization experiments at 1·0 GPa using two different primary magmas representing deep (90 km) and shallow (35 km) mantle extraction depths. Experiments on a hydrous high-Mg basalt were conducted at graphite-saturated and more oxidized conditions (NNO to NNO + 2, where NNO is nickel–nickel oxide buffer) to exploit the influence of f O2 on phase assemblages and the evolution of derivative liquids. The liquid line of descent (LLD) was simulated from liquidus to near-solidus conditions ranging from 1330°C to 720°C. H2 O contents varied from about 2·0 to more than 10 wt %. The LLD covers the entire compositional range from high-Mg basalt to high-silica rhyolite and evolves from metaluminous to peraluminous compositions at 56–60 wt % SiO2 under oxidizing conditions. The observed crystallization sequences and the LLD reveal contrasting behavior depending on oxidation state, H2 O content and equilibrium versus fractional crystallization. Equilibrium crystallization of high-Mg basalt under reducing conditions is initially dominated by olivine fractionation followed by Cr-rich spinel, clinopyroxene (cpx), and orthopyroxene (opx). Finally, between 1060 and 1000°C, amphibole formed by a peritectic reaction consuming cpx + olivine and forming amphibole + opx, resulting in 16% silica-undersaturated trachy-basaltic liquid. Equilibrium crystallization of the same composition under oxidizing conditions is characterized by strongly enhanced olivine and cpx fractionation and suppression of opx only occurring as a result of the peritectic amphibole-forming reaction at and below 1040°C. The liquid at 980°C is a peraluminous, alkali-poor, high-Al andesite representing ∼15% residual liquid. Fractional crystallization of the high-Mg basalt under oxidizing conditions evolves through fractionation of early olivine joined by cpx at 1200°C, followed by opx and hercynitic spinel (1140–1080°C) and amphibole at 1050°C coexisting with cpx (and spinel) to 980°C. At 950°C both garnet and plagioclase (plag) join amphibole as liquidus phases. This paragenesis (plus ilmenite and apatite) persists to 750°C with 16% residual liquid relative to the initial basaltic composition. Liquids evolve continuously from basalt to rhyolite, crossing the metaluminous–peraluminous boundary at about 60 wt % SiO2 . Fractional crystallization of the basaltic andesite starting material differs at high temperature, where opx and cpx are the liquidus phases (1200–1080°C), followed by amphibole at the expense of opx. Below 950°C the phase assemblage is identical except at the lowest temperature (720°C), where quartz saturates in a high-silica rhyolitic liquid representing 20% of the initial basaltic andesite. Liquid compositions of the two starting compositions converge below 950°C, with the exception of K2 O, which behaves incompatibly along the liquid line of descent. The H2 O-undersaturated fractional crystallization experiments on the high-Mg basaltic composition under relatively reducing conditions evolve towards tholeiitic or alkalic compositions owing to early plagioclase (at 1140°C) and abundant opx (at 1110°C) crystallization followed by garnet–cpx–plag–ilmenite at 1080°C. Closed-system equilibrium crystallization under relatively oxidized conditions is characterized by significant expansion of the olivine stability field (>250°C, 1280–1000°C) relative to more reducing conditions, causing depletion of the liquid in ferrous iron and increase of ferric iron. The resulting f O2 of the coexisting basaltic liquids increases by more than 3 log units from about NNO + 2 to NNO + 5·5 over the temperature range >1200–1040°C, potentially offering an explanation for the more oxidized character of hydrous arc magmas as opposed to low-H2 O tholeiitic magmas.